ANTECEDENTS TO THE CAPITAL STRUCTURE OF SERVICE COMPANIES LISTED ON THE IDX IN 2019-2023 - Anggraeni, Reni; Budi, Agung (Univesitas Muhammadiyah Tangerang, 2024)
This research was conducted because of different research results regarding the factors that influence capital structure, especially profitability, asset growth and business risk. By using quantitative descriptive analysis and purposive sampling techniques, the final sample obtained was 8 companies. The data source used is secondary data obtained from the Indonesian Stock Exchange website. The data analysis technique used is descriptive statistics and panel data regression analysis with the help of EViews 11. Based on the analysis results, it shows that profitability and asset growth have no effect on capital structure, while business risk has a negative effect on capital structure.